Epidemiology and determinants of serologically diagnosed hiv-1 and hiv-1&2 in tertiary hospitals of eastern peninsular Malaysia - Muhadi, Siti Aishah (2020)
Introduction: Human immunodeficiency virus (HIV) infection is known as the leading cause of mortality and morbidity worldwide. There are two types of HIV infection, HIV- 1 and HIV-2, which are geographically different in epidemiology and determinants. Objective: To determine the epidemiology and determinants of HIV-1 and HIV-1&2 among HIV patients in tertiary hospitals of Eastern Peninsular Malaysia. Method: A cross sectional study of serologically diagnosed HIV -1 and HIV-1&2 from January 2016 until December 2018 of three tertiary hospitals in Eastern Peninsular Malaysia, aged >12 years were included. Data were obtained from laboratory request forms, medical record folders, Laboratory Information System (LIS) and Hospital Information System (HIS).All collected data were analysed by SPSS version 24 which include descriptive statistic for sociodemographic data, Pearson chi square for association between type of HIV with HCV, HBV, syphilis and tuberculosis and Independent T test for association between type of HIV with haematological parameters. The risk factor associated with HIV-1&2, were determined by Simple Linear Regression Model, variables with p value <0.25 were subjected to Multiple Logistic Regression Model. A p value of <0.05 was considered as statistically significant. Results: Out of 519 serologically diagnosed HIV, 344 (66.3%) were HIV-1 and 175 (33.7%) were HIV-1&2. HIV positive were highly distributed in Malay male, single and worked in nonprofessional sector in both groups. Most HIV-1 patients were presented with tuberculosis. However, HIV-1&2 patients were mostly asymptomatic at diagnosis. The mean age was slightly higher, in HIV-1&2 (39, SD =9) compared to HIV-1 (38, SD=11). The commonest mode of transmission for HIV-1 was by sexual contact 131(45.7%) whereas IVDU 56(45.2%) in HIV-1&2. Co-infection with tuberculosis (p=0.005) and HCV (p<0.001) were significantly higher in HIV-1 as compared to HIV- 1&2. IVDU was a significant determinant to develop HIV-1&2 (Adjusted OR: 3.5, 95% CI=1.875-5.227, p<0.001). Conclusion: Proportion of HIV-1&2 was high in this study. Most HIV-1&2 was asymptomatic at diagnosis and IVDU was the significant determinant of serologically diagnosed of HIV-1&2. Patient with HIV-1&2 present less severe compare to patient with HIV-1. However, further molecular diagnostic study should be tested to confirm the type of HIV in future.